Companions in the Spirit – Companions in Mission: Reflections on Mission and Spirituality (International review of mission, 2012)
Since Pentecost the Holy Spirit has inspired the church to proclaim Jesus Christ as the Lord and Saviour and we continue to be obedient to the command to preach the gospel in all the world. The Holy Spirit anointed the Son of God “to preach good news to the poor, heal the broken-hearted, proclaim liberty to captives, recovery of sight to the blind and set at liberty those who are oppressed” (Luke 4:18). … The ministry of the Holy Spirit – in which the church is privileged to share – is to heal and reconcile a broken world. This text reflects the last step of the work accomplished by the Commission on World Mission and Evangelism (CWME Working Group on Mission and Spirituality from 2008 to 2011). A good number of experts from different cultural and religious contexts have offered their in put during the process. Other papers were produced and published in the International Review of Mission. The process of elaboration of this text has been broadly inclusive in terms of the varied backgrounds and traditions of the people involved. Therefore, it has been enriched by a variety of sensitivities and consequent preferences of language. Although not everybody would use the same expressions and nuances that are used in the text, its main message has gathered significant agreements around key concepts and directions in mission spirituality. Some convictions have accompanied the group in its journey. Spirituality is life in the Spirit, and life in the Spirit is experienced in faith, love and hope. To explore how this becomes real in mission has been the purpose and the challenge this working group faced from the beginning, together with the conviction that the question of pneumatology is one of the more urgent theological issues today. It leads to assuming a trinitarian theology of mission with emphasis on the pneumatological character of God's saving presence. Renewed interest in the Holy Spirit is not only or primarily the work of scholars. It relates to the new attentiveness and receptivity to experiences of the Spirit among the faithful in manysectors: in spirituality and liturgy, in the sense of vocation, apostolic ministries, and prophetic and healing witness in service and works of justice. The main contributions regarding the content of the text point to the fact that pneumatological studies sustain a deep understanding of our life in the Spirit as well as our involvement in mission. They also make evident that a “spiritual” approach to mission is based extensively on biblical foundations. Those contributions refer in one way or another to the challenges to life that the Spirit brings to the mission experience as well as the inescapable need for discernment, prayer and deep renewal of persons and communities. And they offer insights for an understanding of companionship in mission as an experience of the Spirit, a gift we welcome at the heart of our Christian community. A significant event has been at the basis of the text “Companions in the Spirit, Companions in Mission”. A Commission on World Mission and Evangelism (CWME) consultation on Pneumatological Foundations of Mission, held in Kingston, Jamaica (24–28 May 2011), gathered a number of experts who shared their studies on relevant issues, followed by fruitful discussion and motivated spiritual life. After the consultation, a small group prepared the draft text below, which was submitted to the CWME meeting in Accra, Ghana, in November 2011. Let us mention some of the main contributions: Bishop Geevarghese Mor Coorilos, in offering his remarks from the Orthodox tradition, states the trinitarian basis of this study on pneumatology and mission. He addresses the ontological and economic aspects of the Trinity, and he expands on the question of “the liturgy after the liturgy”, pointing, among other aspects, to the need to address ecological issues in this perspective. When it comes to the feminine side of the Spirit, he proposes a beyond-gender dimension. Mary Motte, in her paper “A Pneumatological Framework for Mission”, states that mission understood as participating in the mission of the triune God roots mission in the Trinity. This traces to the early church's efforts to express its experience of Jesus revealing the mystery of God, and of the Spirit inspiring faith and guiding the community. The attempt to sketch a pneumatological approach to mission can resolve that there is a grounding reality available in the Hebrew scripture and in the New Testament, as well as in the patristic era, in which the Spirit is seen consistently accompanying the process of salvation history. Kirsteen Kim's paper, “‘Missio Dei’ as a Pneumatological Paradigm and Mission as Spirituality”, discusses how the mission of the Spirit is also linked to Christ and the incarnation in a truly trinitarian formulation. She deals with mission spirituality as an important corollary of mission pneumatology. And she offers insightful thoughts regarding discernment. She develops four biblical criteria for discernment: ecclesial, ethical, charismatic and liberational, all previously introduced in the Conference on World Mission (Athens, 2005). Remembering the Canberra WCC Assembly, K. Kim considers that mission is a spiritual endeavour and spiritual life is missional, since both are human responses to impulses produced by the mission of the Spirit in the whole creation. Amos Yong, in his paper “Primed for the Spirit: Creation, Redemption, and the Missio Spiritus” , approaches the theology of mission both in terms of the missio Dei more generally and the missio Spiritus more specifically. This text surveys the pneumatological foundations of Christian missiology by identifying the mission, role and work of the Spirit in creation, redemption (in Christ and through the church) and the eschaton. A pneumatological theology of mission includes, according to the author, at least also the following domains: a theology of culture which sees the cultural dimension of human life already imbued with the Spirit's presence and activity, thereby enabling the inculturation and contextualization of the gospel message; a political theology which sees the Spirit is already at work in the public, social and economic spheres of human life, thereby enabling the redemption and transfiguration of these dimensions of human existence according to the gospel of Christ; a theology of religions which views the religious dimension of human life as pointing to and awaiting fulfilment in the gospel of Jesus Christ. María Aránzazu AGUADO